Transition of blood glucose level in a patient with pregnancy‐associated fulminant type 1 diabetes mellitus. Issue 5 (26th October 2020) - Ichikawa, Takahiro; Kitae, Aya; Takeda, Sorou; Sueyoshi, Atsushi; Hamaguchi, Masahide; Fukui, Michiaki
Abstract: We report on the transition in blood glucose levels before and after the onset of fulminant type 1 diabetes mellitus in a perinatal woman. In week 38 of pregnancy, before which the patient had normal glucose tolerance, idiopathic acute pancreatitis was diagnosed. Five days thereafter, she became hypoglycemic, so we closely monitored her blood glucose levels. A total of 13 days later, she was hyperglycemic with a blood glucose level >16.0 mmol/L and glycated hemoglobin of 6.4%. Her fasting serum C‐peptide reactivity level was 3.6 ng/mL on the 5th day, and 0.2 ng/mL on the 18th day. Multiple insulin injection therapy was administered since the 18th day; after that, ketoacidosis did not occur. The patient was diagnosed with fulminant type 1 diabetes mellitus based on hyperglycemia without high glycated hemoglobin levels and sudden onset insulin‐dependent diabetes. Monitoring glucose levels in the case of idiopathic acute pancreatitis during pregnancy and prompt initiation of insulin therapy are important. Abstract : Fulminant type 1 diabetes is a severe disease in which oversight results directly in the death of the patient. This is a rare case observing how fasting and preprandial blood glucose levels change before and after the onset of pregnancy‐associated fulminant type 1 diabetes. During the therapeutic process for idiopathic acute pancreatitis in pregnancy, treating physicians should closely monitor blood glucose levels, which might lead to early diagnosis of fulminant type 1 diabetes.